A mathematical model for fluid-glucose-albumin transport in peritoneal dialysis - Cherniha, Roman; Stachowska-Piętka, Joanna; Waniewski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
A mathematical model for fluid and solute transport in peritoneal dialysis is constructed. The model is based on a three-component nonlinear system of two-dimensional partial differential equations for fluid, glucose and albumin transport with the relevant boundary and initial conditions.
Keywords: fluid transport; transport in peritoneal dialysis; nonlinear partial differential equation; ordinary differential equations; steady-state solution